Demythologizing Neraka Huthomah - Irfan Afandi (IAI Darussalam, 2016)
Demythologization is one of the processes that look for assumptions that are the mythological religious reasons for the assumption of modern reasons. Assuming this is expected to exclude other meanings of the kerygma or the divine message from religious reasoning. This article seeks to apply in the case of Hutomah which is generally regarded as one hell. The process of demythologizing Hellomah's hell in Qs. al-Humazah finds a (significant) maghza that Hutomah not only responds to humazah and lumazah behavior but also the circumstances and situations that result. With this process can be found a more suitable meaning and strive to make the Qur'an more contextual and reflective